2017
DOI: 10.1016/j.carbon.2016.12.097
|View full text |Cite
|
Sign up to set email alerts
|

Brodie vs Hummers graphite oxides for preparation of multi-layered materials

Abstract: Graphite oxides synthesized by one and two step Brodie oxidation (BGO) andHummers (HGO) methods were analysed by a variety of characterization methods in order to evaluate the reasons behind the difference in their properties. It is found that the Brodie method results in a higher relative amount of hydroxyl groups and a more homogeneous overall distribution of functional groups over the planar surface of the graphene oxide flakes. The higher number of carbonyl and carboxyl groups in HGO, detected by several m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
93
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 120 publications
(113 citation statements)
references
References 55 publications
12
93
0
Order By: Relevance
“…[60] Nearly the same d(001) of 9.93 Å and 9.96 Å are found for BGO intercalated with xylitol and sorbitol, Next set of experiments was performed using in situ synchrotron radiation XRD recorded during the heating of BGO mixed with xylitol or sorbitol. The first heating cycle was performed up to 400 K to verify the structure of BGO in molten sugar alcohol and keeping temperature below the point when thermal deoxygenation of GO could be expected (~>130 0 C, [60]), Figure 2a. Analysis of XRD data shows that the same phase with d(001) ~ 9.9 Å is formed in molten sugar alcohols.…”
Section: Resultsmentioning
confidence: 79%
See 2 more Smart Citations
“…[60] Nearly the same d(001) of 9.93 Å and 9.96 Å are found for BGO intercalated with xylitol and sorbitol, Next set of experiments was performed using in situ synchrotron radiation XRD recorded during the heating of BGO mixed with xylitol or sorbitol. The first heating cycle was performed up to 400 K to verify the structure of BGO in molten sugar alcohol and keeping temperature below the point when thermal deoxygenation of GO could be expected (~>130 0 C, [60]), Figure 2a. Analysis of XRD data shows that the same phase with d(001) ~ 9.9 Å is formed in molten sugar alcohols.…”
Section: Resultsmentioning
confidence: 79%
“…Detailed characterization of precursor graphite oxides used in this study (BGO and HGO) was performed in our earlier study [60]. Both materials showed similar oxidation degree (C/O=2.7 and C/O=2.6 respectively) but rather different vapour sorption properties, thermal stability (revealed by TGA), certain difference in FTIR and NMR spectra.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Flakes obtained from direct exfoliation of graphite (e.g., by liquid phase exfoliation [6,7]) have more regular structure and better conductive properties, and are therefore more suitable for electronics applications, but are also more expensive and difficult to obtain and handle. Therefore, for the 3D scaffold building, usually, the process starts from the oxidation of graphite to graphite oxide, e.g., by Hummer's method [38], followed by exfoliation-reduction either thermally [39], leading to Thermal Exfoliate Graphite Oxide (TEGO), or using microwaves, leading to Microwave Exfoliate Graphite Oxide (MEGO) [40,41], resulting in materials with SSA usually not exceeding 800 m 2 /gr [42,43]. Samples can be subject to additional treatments, such as further reduction, or chemical activation (e.g., with KOH), which modify the edges with the result of increasing the porosity to specific pore volume (SPV) greater than 2 cm 3 /g [30,44] and improving the SSA up or exceeding the graphene limit (2630 m 2 /g).…”
Section: Graphene-based Nano-porous Materials: Production and Computementioning
confidence: 99%
“…At a low degree of oxidation, hydroxyl groups can chemically turn into epoxide groups and vice versa, allowing for the use of GO for specific technological applications [24]. In addition, the GO structure reveals a mixed sp 2 −sp 3 hybridization as a direct consequence of the degree of oxidation acquired during the oxidation process [26] (see, e.g., Brodie [27], Staudenmaier [28], Hummer [29], Marcano [30], and Chen [31]). Hummer et al reported the method most used nowadays: the oxidation of graphite is realized by treatment with KMnO 4 and NaNO 3 in concentrated H 2 SO 4 .…”
Section: Introductionmentioning
confidence: 99%